Na+ entry through heteromeric TRPC4/C1 channels mediates (−)Englerin A-induced cytotoxicity in synovial sarcoma cells. Issue 1 (December 2017) - Muraki, Katsuhiko; Ohnishi, Kaori; Takezawa, Akiho; Suzuki, Hiroka; Hatano, Noriyuki; Muraki, Yukiko; Hamzah, Nurasyikin; Foster, Richard; Waldmann, Herbert; Nussbaumer, Peter; Christmann, Mathias; Bon, Robin; et al.
Abstract The sesquiterpene (−)Englerin A (EA) is an organic compound from the plantPhyllanthus engleri which acts via heteromeric TRPC4/C1 channels to cause cytotoxicity in some types of cancer cell but not normal cells. Here we identified selective cytotoxicity of EA in human synovial sarcoma cells (SW982 cells) and investigated the mechanism. EA induced cation channel current (Icat) in SW982 cells with biophysical characteristics of heteromeric TRPC4/C1 channels. Inhibitors of homomeric TRPC4 channels were weak inhibitors of the Icat and EA-induced cytotoxicity whereas a potent inhibitor of TRPC4/C1 channels (Pico145) strongly inhibited Icat and cytotoxicity. Depletion of TRPC1 converted Icat into a current with biophysical and pharmacological properties of homomeric TRPC4 channels and depletion of TRPC1 or TRPC4 suppressed the cytotoxicity of EA. A Na+ /K+ -ATPase inhibitor (ouabain) potentiated EA-induced cytotoxicity and direct Na+ loading by gramicidin-A caused Pico145-resistant cytotoxicity in the absence of EA. We conclude that EA has a potent cytotoxic effect on human synovial sarcoma cells which is mediated by heteromeric TRPC4/C1 channels and Na+ loading.